Earthquake Behavior of Berke Arch Dam Using Ambient Vibration Test Results - Sevim, Baris; Altunisik, Ahmet Can; Bayraktar, Alemdar (ASCE-AMER SOC CIVIL ENGINEERS, 2012)
The Berke Arch Dam is the highest arch dam constructed in Turkey. The dam height is 201 m, and the crest length is 270 m. This paper describes the Berke Arch Dam, its finite-element modeling, ambient vibration testing, finite-element model calibration, and earthquake behavior before and after model calibration. First, three-dimensional (3D) models of dam-reservoir-foundation interaction were developed to obtain analytical dynamic characteristics, such as natural frequencies and mode shapes using the Ansys finite-element program. In the analyses, reservoir water was represented by a Lagrangian approach. Then, ambient vibration tests were conducted on the dam on 4 days in May 2009 to obtain experimental dynamic characteristics. In ambient vibration tests, the sensitive accelerometers were placed on several points on the arch dam, and signals were collected from accelerometers. The enhanced frequency domain decomposition technique was used in the extraction of experimental natural frequencies, mode shapes, and damping ratios. After that, 3D finite-element models of the Berke Arch Dam were calibrated using ambient vibration test results. Finally, earthquake behaviors of initial and calibrated models of the Berke Arch Dam were obtained using the Adana-Ceyhan Earthquake in 1998. It was observed that model calibration affects the results considerably. DOI: 10.1061/(ASCE)CF.19435509.0000264. (C) 2012 American Society of Civil Engineers.
Keywords: Ambient vibration testing; Berke Arch Dam; Dynamic characteristics; Earthquake behavior; Finite-element modeling; Model calibration; NONORTHOGONAL SMEARED CRACK; NATURAL FREQUENCIES; DYNAMIC-RESPONSE; MODELS; Construction & Building Technology; Engineering